IMPLEMENTASI LESSON STUDY PADA MATA KULIAH ANALISIS REAL PROGRAM STUDI PENDIDIKAN MATEMATIKA - Darma Ekawati; Jumarniati Jumarniati (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2018)
This research is a descriptive study that aims to learn about the activities and abilities of students in learning real analysis. Subject in this study were students on semester VI of academic year 2016/2017. This research implement cooperative learning model through lesson study in real analysis subject that held in March and April 2017. Data was collected by planning, implementation, and reflection (see). This research was conducted to observe the increase in the activities and abilities of students in each cycle. The general-stage of this research is: (a) formulates student abilities, (b) observes research subjects, (c) performs data collection, (d) performs data analysis in each cycle, (e) performs discussion of analysis results, (f) performs the conclusions. Results of the study are (1) the activities of students using cooperative learning models through lesson study in the real analysis subjects are increasing; (2) the ability of students to solve real analysis problems are improved; (3) lecturer and student need to create good circumstances to motivate student; (4) Lecturer get suggestion from colleagues to improve the quality of learning. Keywords: Cooperative learning model, Lesson study, Activity, Analysis Real.